The effect of “coyolillo” (Cyperus rotundus) on the growth of canavalia (Canavalia ensiformis). - Lara, Francisco; Serrano, Leopoldo; Aguirre, Carlos; Villatoro, Raúl (Agronomía Mesoamericana, 2016)
During the summer 1995, at the Experimental and Training Station of the Agronomy School of the University of El Salvador, an experiment was established by alternating sword bean (0.80 m. x 0.50 m) with maize (0.80 m. x 0.30 m.), under zero management. The plot was divided in two areas one with a high infestation of “coyolillo” and other with a predominance of wide-leaf weeds, such as Baltimora recta, Melantera sp., Lantana camara, and Panicum sp. Samples were taken in each area every 10 days, by using 10 sword plants to determine the following variables: plant height, dry weight, absolute growth rate, and relative average growth rate. The infestation with Cyperus initially oscillated between 1200 to 1650 young sprouts/m2. The experiment was analyzed under the concept of paired plots. The results indicated significant differences for the height of Canavalia plants, increasing from 10 dds to 20 and 30 dds, reaching the maximum growth in the plot without Cyperus, reaching 108 cm at 40 dds, in contrast with plants with competence by Cyperus, which attained a maximum height of 82.9 cm. This showed an unfavorable competition to Canavalia, which was also supported by the accumulation of dry matter.